PENINGKATAN POTENSI DESA TANJUNGKENONGO KECAMATAN PACET KABUPATEN MOJOKERTO MENUJU DESA WISATA (Jurnal ABDI Bhayangkara, 2020)
The development of technology and information systems in this era is very helpful in increasingthe pace of the economy. The fact, in rural areas still minimal use of technology and internet-basedinformation systems to help marketing their products. Traditional marketing is a tool that they stilluse, by selling their products to broker’s or waiting for buyers to buy their product. Therefore, wewant to focus more on improving the quality of human resources in Tanjungkenongo Villagethrough activities, such as (1) Counseling on technology-based marketing methods throughapplications such as WA, IG, and Facebook. (2) Counseling on packaging and branding methodsso the product becomes more attractive (3) Planting tabebuya seeds to improve the aesthetics ofTanjungkenongo Village in the future (4) Provision of chili, tomato, and moringa seeds toTanjungkenongo villagers in order to benefit the residents in the future. The counseling of theabove activities was carried out for PKK communities in Tanjungkenongo Village, with the aimthat they could make the most of the potential of natural resources in Tanjungkenongo Village.